Does Spotted Pumpkin (Lagenaria Breviflora R.) Positively Affect the Health Status of Broiler Chicken? - EKUNSEITAN, Deji; Odubela, Oluwabamise V.; Ahmed, Ridwan A.; Iyasere, Oluwaseun S.; Adeniran, Boluwatife A. (Polish Journal of Natural Sciences, 2025)
Two hundred and eight (208) day-old Cobb chicks hatchery-infected with Eimeria were divided into four treatment groups and administered: control (0), 50 ,100 and 150 grams of Lagenaria breviflora R. (Lb) whole fruit per litter of water thrice a week for 6 weeks. Data were obtained on faecal count, haematological indices, serum metabolites and stress biomarkers. There was reduction in Eimeria count as Lb increased with the highest reduction (85.20%) in 150 g. The highest (P < 0.05) packed cell volume, haemoglobin and red blood cell count was observed in 150 g while white blood cell count was highest (P < 0.05) in 50 and 150 g. Total protein was highest (P < 0.05) in 150 g, globulin was highest in 100 and 150 g LB while the serum stress biomarkers (SOD and GSH-Px) was least in 50 g. The use of Lb up to 150 g can used in eradicating coccidiosis without compromise on health of birds.